(untitled) (American Journal of Youth and Women Empowerment, 2024)
The ultimate goal of microfinance service is to eventually give impoverished people an opportunity to become self-sufficient by empowering in particular Women, as many microfinance organizations do. The role of microfinance institutions has been extended beyond women’s economic empowerment such that have the potential to make significant contributions to gender equality and promote sustainable livelihood and better working conditions to poor women. The study attempted to find out women empowerment factors and indicators that should be enhanced by microfinance services, the mode of loan application, and the extent to which women food vendors are impacted by loans on profit as far as Shinyanga Municipal council is concerned. The study engaged a sample size of 92 youth and adult women. Majority of women food vendors interviewed have been operating the business for more than 10 years and had applied for loan that amounted below TZS 1,000,000/-. It is evident that women prefer to apply loans from microfinance institutions in groups rather than individually. The impact of loans on profit was also tested before and after loan acquisition. The results show that after acquiring loans women had increased their monthly earnings to an average of TZS 3,000,000/- and play a dominant part in decision making at both household and community levels because of their status core. The findings reveal that community members recognize the reduction of interest rates, reduction of harsh conditions, and the provision of entrepreneurship skills as key components of empowerment factors. On empowerment indicators, the survey found that women have access to and control over resources, and women who earn huge income were likely to play a dominant part in decision making. Further, the survey reported that women have full freedom to spend their earnings as they wish.